An investigation on using pre-treated tyre rubber as a replacement of synthetic polymers for bitumen modification - Subhy, Ayad; Lo Presti, Davide; Airey, Gordon (Taylor & Francis, 2015)
Rubberized bitumen obtained through a swelling process, has widely proven to be a successful technology for asphalt pavement applications and a solution to reduce the dismantling of tyre rubber on landfills. However, this technology presents two main operative issues which needs the adoption of costly special equipment. Firstly, significant high value of High Temperature Viscosity (HTV) which imposes mixing and compaction difficulties and leads to increased energy consumption and emissions. Furthermore, during the hot storage period, phase separation between rubber particles and the base bitumen could occur. Developing Recycled Tyre Rubber Modified Bitumen (RTR-MBs) with improved storage stability and reduced values of HTV could allow using this technology in standard asphalt plants, resulting in an environmental-friendly and cost-effective option of standard Polymer Modified Bitumen (PMBs). In this study, two different pre-treated and one straight ambient recycled rubbers were used to produce RTR-MBs. The first RTR was pre-treated by special oil and Warm Mix Additives (WMA) and the second was partly devulcanised. Also, two base binders were selected with large differences in mechanical properties in order to identify the effect of base binder. The high temperature viscosity was successfully reduced by using pre-treated RTR. The use of RTR together with Fischer–Tropsch wax (Sasobit®) in bitumen technology offered superior high in-service temperature properties and reduced value of HTV, and thus can be preferred option over styrene–butadiene–styrene (SBS) modification.